[Impact of menarche age on the near-term and long-term obesity of adult females] - Wei, X; Hua, Y; Lu, Y; Hu, Y; Bian, Z; Guo, Y; Chen, Z; Li, L (Chinese Journal of Epidemiology, 2019)
Objective: To study the relationship between the age of menarche and the near-term/long-term obesity in adult women. Methods: We analyzed the baseline data of 30 895 women with complete data on menarche and body measurement that was from the China Kadoorie Biobank (CKB) study from 2004 to 2008. The age of menarche was divided into three groups: ≤12, 13-16 and ≥17 years old. Prematurity was set at age ≤12 years. Multivariate logistic regression was used to analyze the effects of menarche age on the near/long-term obesity in female adults. Results: The average menarche age of respondent appeared as (15.64±1.92) years old, with prematurity number as 1 421, accounting for 4.6% of the total numbers. Regarding the postponing of dates of birth, the age of menarche in women showed an advancing tendency. Among all the adult women under study, 803 developed near-term obesity, with the prevalence as 2.6%, while the number of long-term obesity was 3 738, accounting for 12.1%. Refining factors of age, lifestyle, menopausal status, hypertension and diabetes showed that the menarche age was related to the risks of both short-term and long-term obesity in women and the ORs (95%CI) were 2.45 (1.74-3.45) and 1.99 (1.69-2.34), respectively. There was no multiplicative interaction shown between the menarche age and menopausal status on long-term obesity (P=0.324). Conclusion: Premature menarche appeared a risk factor for near-term/long-term obesity in adult females.